Enhancing Social Solidarity And Self-Reliance Through The Distribution Of Basic Food Aid At Al Amani Orphanage Batam City - Mulyadi, Tirta; Ilham, Wahyudi; Hari Sandi; Yusakh Yama Langi; Bowen Algren Wuysang (JURNAL KEKER WISATA, 2025)
This community engagement initiative was designed to enhance social cohesion and promote self-sufficiency among the residents of the Al Amani Orphanage in Batam City through the structured distribution of staple food packages. The program emerged from the pressing need to assist economically disadvantaged children while simultaneously cultivating a spirit of collective responsibility and empathy within the broader community. The implementation involved not only the delivery of essential food supplies but also the facilitation of educational activities aimed at reinforcing the importance of mutual support and shared social values. Furthermore, the initiative encouraged the development of sustainable, community-based self-help practices. The outcomes of this program suggest that beyond fulfilling immediate nutritional needs, the activities contributed significantly to raising social awareness, reinforcing the ethos of social care, and fostering collaborative engagement. This demonstrates that even small-scale, community-driven interventions possess the potential to meaningfully contribute to the construction of inclusive, compassionate, and resilient social structures. Keywords: Community Engagement, Social Cohesion, Al Amani Orphanage